2005
DOI: 10.1007/s00542-005-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically driven synthetic microjet arrays as a propulsion method for micro flight

Abstract: A novel propulsion method suitable for micromachining is presented that takes advantage of Helmholtz resonance, acoustic streaming, and eventually flow entrainment and thrust augmentation. In this method, an intense acoustic field is created inside the cavity of a Helmholtz resonator. Flow velocities at the resonator throat are amplified by the resonator and create a jet stream due to acoustic streaming. These jets are used to form a propulsion system. In this paper a system hierarchy incorporating the new met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Figure 17 presents the variation of the calculated virtual viscosity [Eq. (8)] of the three actuators with stroke ratio. The eddy viscosity of the equivalent continuous jet is also shown for comparison.…”
Section: B External Flowfield 1 Schlichting Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 17 presents the variation of the calculated virtual viscosity [Eq. (8)] of the three actuators with stroke ratio. The eddy viscosity of the equivalent continuous jet is also shown for comparison.…”
Section: B External Flowfield 1 Schlichting Modelmentioning
confidence: 99%
“…Additionally, the periodic vortex rings introduced into the flow exhibit an ability to influence the environment at a variety of length scales. All of these properties make synthetic jets attractive in a number of applications that include active flow control [2][3][4], electronic cooling [5,6], fluid mixing [7], and aerial [8][9][10][11] and underwater propulsion [12,13]. Although recent reviews of synthetic jets may be found in the literature [14][15][16], a brief overview of the background relevant to the present investigation is presented next.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, the ZNMF jet actuator can be highly integrated by MEMS technique with the development of material science and manufactory technique. Figure 24 presents the newly invented micro ZNMF jet actuator by Parviz et al [68] of Michigan University. The wafer contains about 1000 resonators configured in four individually addressable quadrants.…”
Section: Application Of Znmf Jet Flow Control On Air Vehiclesmentioning
confidence: 98%
“…The wafer integrated with ZNMF jet actuators, next to a US quarter coin [68] . In the section at r/R=0.71, a closed recirculation flow region is formed on the surface of the stator vane down stream of the obstruction without control, and the ZNMF jet actuator just reduces the extent of the recirculation region.…”
Section: Figure 24mentioning
confidence: 99%
“…Recent advances in microfabrication and microelectromechanical systems (MEMS) have enabled the fabrication of individual devices that can perform some of the above functions such as microactuation [1] and microsensing [2]. Other functions performed by Drosophila such as self-healing, energy storage/conversion and flight in a miniature system measuring only a few millimeters have proven more difficult to replicate [3,4]. Despite the ability of solidstate microfabrication technology to construct advanced devices, the level of complexity in multifunctional system integration inherent to Drosophila is far beyond the state-of-the-art in microengineering.…”
Section: Introductionmentioning
confidence: 99%